(3GdMb GdeHjf aj GdaQb Hjf GdTjYI hGdehGdjf ebOeIs - (3GdHQGbj, GdMSfj, GdfLaj, MqShf, MSjf Hf CMeO Hf GdMSjf Hf ESeGYjd, J (B1332 (3g`s ((3HNW eDdagGs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B...(3deG QCjJ GdCNHGQ GdcKjQI GdhGQOI Yf Bd eMeO aj aVd GdTjYI(B...s
(3BNQgG (B:s
...(3bdJ heG GdHQRN? bGd GdbHQ efP Mjf ehJg Edi jhe GdbjGeI (B...(3hgPG BNQ eG CQOfG LeYg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B233s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B601s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds